Relationship of Effective Size to Hatchery Supplementation and Habitat Connectivity in a Simulated Population of Rio Grande Silvery Minnow. (30th July 2020) - Carson, Evan W.; Osborne, Megan J.; Turner, Thomas F.
Abstract : Simultaneous management actions often are used to improve the status of imperiled species, yet the effects of these actions can be difficult to determine. The endangered Rio Grande Silvery Minnow Hybognathus amarus is a short‐lived fish with a dispersive life history and thus requires—but does not occupy—unfragmented habitat for recruitment and survival. We used Rio Grande Silvery Minnow as a model system for an individual‐based simulation study to evaluate responses of genetic effective size to hatchery supplementation and fish passage in a managed population. Simulations were designed to test effects of fish passage on the relationship between estimates of inbreeding ( N eI ) and variance ( N eV ) effective sizes, which differ consistently ( N eI >> N eV ) in long‐term genetic‐monitoring data from hatchery‐supplemented Rio Grande Silvery Minnow populations. Values of different effective population size measures should be identical in a demographically stable and connected (admixed) population but can differ substantially under nonequilibrium conditions. When a barrier prevented upstream dispersal, N eI was associated negatively with rate of downstream dispersal and positively with supplementation rate, whereas N eV was associated negatively with both. This mirrored observations from Rio Grande Silvery Minnow. Individual effects of dispersal and supplementation, however, were difficult to discern due to significant interaction between these factors. When connectivity was restored, N eI and N eV depended on supplementation rate, with positive association between N eI and supplementation rate versus a negative association for N eV and interaction terms, and effects of dispersal were nonsignificant. Although fish passage did not alter the difference between N eI and N eV, our study suggests that for Rio Grande Silvery Minnow, and potentially other intensively managed species in regulated rivers, fish passage may help to distinguish effects of management actions, such as supplementation, from effects of other demographic influences. More generally, explicit analytical consideration of differences in effective population size estimates can provide important details of genetic responses to management.